Control interno en la Inmobiliaria Consvivisa S.A en la ciudad de Babahoyo - Torres Baldeon, Bryan Josue (2020)
This case study is carried out at the company Consvivisa SA, a private company belonging to Mr. Jorge Emilio Marún Ramírez as legal representative, is located in Babahoyo, located at Km ½ via Chilintomo, to find out how the internal control of it, which has been affected with problems such as organizational communication, work environment, teamwork, control of entries and exits, among other negative factors that directly affect employees who work in the institution and therefore its effective and efficient performance.